Laporan Pengabdian Masyarakat Daerah Binaan Penyuluhan Penyiapan Reproduksi Sehat Remaja Dalam Mencegah Stunting Di Desa Loru Kecamatan Sigi Biromaru Tahun 2022 - Enggar Enggar; Sriventi Lestari; Lia Lia (Universitas 45 Surabaya, 2023)
Stunting is a condition in which a person has less length or height compared to the general population. (Oktavia, 2020). Stunting is a condition in which a person's height is shorter than the height of other people in general or the same age. (Atikah & Rahayu, 2018). Stunting cases are a global problem, not only in Indonesia. According to (Hoffman et al, 2013). Stunting is a form of growth failure (growth faltering) due to accumulation of insufficient nutrition that lasts a long time from pregnancy to 24 months of age (Mustika & Syamsul, 2018).